Gestational diabetes mellitus yesterday, today and tomorrow: A 13 year italian cohort study. (September 2020) - Bordin, Paolo; Dotto, Luciana; Battistella, Liliana; Rosso, Elena; Pecci, Lucia; Valent, Francesca; Collarile, Paolo; Vanin, Michele
Abstract: Aims: To describe all cases of gestational diabetes mellitus (GDM) managed at the Italian Hospital of San Daniele del Friuli from 2006 to 2018, after the establishment of a dedicated multidisciplinary team. Methods: Data on mothers, pregnancies, and newborns have been recorded since the team establishment. The associations of maternal, pregnancy, and delivery characteristics with complications of pregnancy and delivery and adverse birth outcomes were assessed. Results: 894 cases of GDM were observed, representing 6.8% of all deliveries. More than 20% of women were non-Italian, 5.3% had a previous macrosomic child, 12.5% previous diabetes or GDM, 27.3% family history of diabetes. On average, women had 4 visits at the clinic; mean glycated hemoglobin was 5.3%; starting body mass index (BMI) 26.2 and weight gain 10.3 kg. Cesarean sections were 21.8%. Pre-eclampsia was the most common pregnancy complication (4.7%). 6.0% of newborns were macrosomic and there were 3 fetal deaths. Only 26.3% of women had a post-partum oral glucose tolerance test. Initial BMI, weight gain, nationality, family history of diabetes or previous diabetes-related pregnancy complications were associated with pregnancy complications or adverse outcomes. Conclusions: We identified factors to be targeted for preventing GDM complications. Further efforts should be directed at post-partum.